Greek Christian epitaphs from Charakmoba and the Land of Moab - Aliquot, Julien (Palestine exploration quarterly, 2020)
Fifteen Greek inscriptions recently discovered in the Land of Moab (southern Jordan) are published here. All are Christian epitaphs, engraved on limestone funerary stelae of an extremely common type at Al-Karak (ancient Charakmoba) and on the surrounding plateau, which bring new information on the onomastics and funerary customs of the local communities in Late Antiquity. An epigram that contains phrases directly borrowed from the epic code of the time is also remarkable. Like the other, less sophisticated, inscriptions discussed here, it testifies to the late and partial Hellenization that characterized the history of the Land of Moab in the Byzantine period.